Penggunaan Multimedia Flipbook Untuk Meningkatkan Hasil Belajar Sejarah Peserta Didik Kelas XI SMAN 10 Banjarmasin - Fatmawati, Tiara; Syaharuddin, Syaharuddin; Prawitasari, Melisa (Lambung Mangkurat University, 2023)
Electronic school books are one of the widely used learning media, but naturally, they look more attractive with audio, video, and image features that make it easier for students to understand the material presented so that student learning outcomes can increase. So that this researcher has a goal to (1) see the results of using a digital multimedia flipbook in improving student learning outcomes in class XI history subjects (2) to find out student responses to the use of flipbooks as a learning medium applied to subjects history. This study uses a quantitative method with a quasi-experimental research design (quasi-experimental), to determine the increase in student learning outcomes using t-test analysis techniques by comparing students pretest learning outcomes with post-test, using two classes, namely experimental class and control class. Based on the results of the study, it shows that the learning outcomes ofstudents’ learning outcomessults of the pretest and post-test, the average result of the pretest score is 60.31 and the average result of the control class score is 60.14. After carrying out a treatment in the experimental class that uses flipbook in learning, the average post-test score is 81.65 and for the control class that does learning without giving treatment, it shows an average score of 61.58. Based on the results of the post-test using the t-test, a significant value of Sig. (2-tailed) 0.00 < 0.05, it means that Ha isaccepted and it means that there is a difference between the use of multimedia flipbook in learning with learning without a multimedia flipbook